Pengembangan Media Video Animasi Berbasis Aplikasi Powtoon Pada Tema 7 Subtema 2 di Kelas V SDN 101610 Purbabangun T.A 2022/2023 - Harahap, Ade Yulis; Simanungkalit, Erlinda; Sembiring, Masta Marselina; Mailani, Elvi; Rozi, Fahrur; Faisal, Faisal; Handayani, Dila (Universitas Labuhanbatu, 2023)
This research is motivated by the use of media in the learning process that is less skilled and creative and only uses makeshift media. This study aims to produce a valid, practical and effective powtoon-based animated video media in supporting learning success. This research is research and development using the 4D development model (define, design, development and dissemination). The subjects of this study were fifth grade students at SD Negeri 101610 Purbabangun and the object of this research was the animated video media based on the powtoon application. The results showed that the validation by material experts in stage I before revision obtained a percentage of 56.9% in the